New Approaches to Comparative Societal Analysis - Berezin, Mabel (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
This course is a graduate seminar designed for students in sociology, political science, and history. It is offered jointly in the sociology and government department. Over the years, I have taught various iterations of this seminar. It has three goals: first, to show that qualitative research and writing is (and should be) as rigorous as quantitative research and writing; second, to acquaint students with a combination of new and classic work in the field; and third, to push students in the direction of designing their own research projects. In the Cornell government department, it meets the requirement for a methods course.